Efektifitas dan Keamanan Pretomanid dalam Pengobatan Tuberkulosis Lini Kedua - Heryanti Pusparisa; Fauna Herawati (Universitas Malahayati Lampung, 2022)
ABSTRACT Tuberculosis (TB) is a serious threat to public health around the world. Recent advances in drug development and new regimens give hope that tuberculosis (TB) treatment is well tolerated, effective, and has a shorter duration. This review includes drug trials and new TB regimens with activity against drug-sensitive and drug-resistant bacilli, optimizing safety. Combination therapy is an approach that has successfully treated tuberculosis in patients who are susceptible to Mycobacterium tuberculosis. The emergence of resistant strains requires the identification of new effective therapies. Current 6-month tuberculosis (TB) therapy is less than optimal with significant side effects and problems with poor patient adherence to medications. The problem of drug-resistant TB is increasing the need to develop new and more effective drugs. Significant advances are being made with several new drug candidates in clinical trials. The literature search process is carried out using the PUBMED database and the keywords